1994
DOI: 10.1523/jneurosci.14-11-06652.1994
|View full text |Cite
|
Sign up to set email alerts
|

Song-induced ZENK gene expression in auditory pathways of songbird brain and its relation to the song control system

Abstract: The ZENK gene encodes a zinc-finger-containing transcriptional regulator and can be rapidly activated in songbird brain by presentation of birdsong (Mello et al., 1992). Here we map the areas of the songbird forebrain that show this genomic response to birdsong, using in situ hybridization. After 30 min of song presentation ZENK mRNA levels reach a peak in the caudomedial telencephalon, in areas adjacent to or closely related with primary auditory structures. These areas include subfields of field L (L1 and L3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
320
2

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(345 citation statements)
references
References 43 publications
(69 reference statements)
23
320
2
Order By: Relevance
“…Several additional nuclei have been identified in songbirds that are important for auditory processing or are related to song learning and control, including the lateral magnocellular nucleus of the anterior neostriatum (lMAN or LMAN; Fig. 7D), the medial magnocellular nucleus of the anterior neostriatum (mMAN or MMAN), and the caudomedial neostriatum (NCM; Nottebohm et al, 1976;Bottjer et al, 1989;Mello et al, 1992;Mello and Clayton, 1994;Margoliash, 1997;Nordeen, 1997;. With the renaming of neostriatum, the name for each of these is altered by substituting nidopallium for neostriatum, and the established abbreviation remains the same (Table 4).…”
Section: Rationale For Individual Changes: the Neostriatummentioning
confidence: 99%
“…Several additional nuclei have been identified in songbirds that are important for auditory processing or are related to song learning and control, including the lateral magnocellular nucleus of the anterior neostriatum (lMAN or LMAN; Fig. 7D), the medial magnocellular nucleus of the anterior neostriatum (mMAN or MMAN), and the caudomedial neostriatum (NCM; Nottebohm et al, 1976;Bottjer et al, 1989;Mello et al, 1992;Mello and Clayton, 1994;Margoliash, 1997;Nordeen, 1997;. With the renaming of neostriatum, the name for each of these is altered by substituting nidopallium for neostriatum, and the established abbreviation remains the same (Table 4).…”
Section: Rationale For Individual Changes: the Neostriatummentioning
confidence: 99%
“…However, analysis of the expression of immediate early genes (IEGs), a measure of neuronal activation (Sagar et al, 1988;Tischmeyer and Grimm, 1999;Davis et al, 2003), has revealed that other parts of the brain are involved in song perception. These brain regions include the caudomedial neostriatum (NCM) [also known as the caudomedial nidopallium (Reiner et al, 2004)] and the caudomedial hyperstriatum ventrale (CMHV) (or caudomedial mesopallium in the new nomenclature of Reiner et al, 2004) (Mello et al, 1992;Mello and Clayton, 1994;Jarvis and Nottebohm, 1997;Mello and Ribeiro, 1998;Bolhuis et al, 2000) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have investigated the expression of immediate early genes (IEGs) (12,13) in adult zebra finch males after exposure to unfamiliar conspecific song (14)(15)(16)(17). Expression of IEGs is a measure of neuronal activation (12,13).…”
mentioning
confidence: 99%
“…Exposure of adult zebra finch males to conspecific song led to significantly increased expression of the IEG known as ZENK in the caudal part of the neostriatum (NCM) and of the hyperstriatum ventrale (cHV), but not in HVC, Area X, lMAN or RA, nor in Field L, a primary auditory projection area (14)(15)(16)(17)(18)(19)(20). The increase in ZENK expression did not occur after exposure to heterospecific song or to tone busts (14,15). Subsequent studies suggest a dissociation between the neural substrates of production and perception of song (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation